The influence of start position, initial step type, and usage of a focal point on sprinting performance - Dysterheft, J. L.; Lewinski, W. J.; Seefeldt, D. A.; Pettitt, R. W. (International Journal of Exercise Science, 2013)
For many athletes, sprinting acceleration is vital to sport performance. The purpose of this study was to observe the influences of starting position, type of initial step taken, and a focal point on sprinting velocity, stride length, and acceleration over a 9.1 m distance. Two trials of four conditions were video recorded in which subjects had no focal point (n = 10) or a lateral focal point (n = 9). The four conditions were: forwards (control), backwards, 90° left (90°L), and 90° right (90°R). Lower velocities (p > 0.05) were observed with focal point usage from the 90°R and 90°L starting positions. Four initial steps were observed during the forwards, 90°L, and 90°R conditions: backwards step, anterior tilt with forward step, pivot-crossover step, and lateral side step. The use of a backwards step resulted in an increased velocity (+0.80 m·s-1, p < 0.01) for the 90° turn trials and increased acceleration (+ 0.37 m·s-2, p < 0.01). Our results indicate that looking at a target can cause a decline in sprint velocity and acceleration over a short distance. Moreover, utilizing a backwards step to initiate a 90° turn may generate more power and force, increasing their velocity for short sprints. We recommend training athletes with a target or focal points to help combat the reduced speed and initiate movement with initial backwards step.